ДОВІРА У ВАЛЮТНО-ФІНАНСОВИХ ВІДНОСИНАХ НА СВІТОВОМУ І НАЦІОНАЛЬНОМУ РИНКАХ (Світ фінансів, 2017)
Куриляк В. Є. Довіра у валютно-фінансових відносинах на світовому і національному ринках. Розглнуто довіру як фактор, який визнає суттєвий вплив на функціонування фінансових ринків. Сформульовано теоретичні підходи до забезпечення довіри учасників ринку. Обґрунтовано тенденції і закономірності формування довіри на українському і світовому фінансовому ринку. Kurylyak V. Trust as a factor of development of monetary and financial relations at the global and national markets. The trust is considered as a factor that influences significantly at the functioning of financial markets. Theoretical approaches for ensuring the trust between market participants are formulated. Substantiated the trends and patterns of trust in the Ukrainian and world financial market. The trends and patterns of trust forming at the Ukrainian and world financial markets are substantiated.